Usefulness of Tranexamic Acid Administration During Sagittal Split Ramus Osteotomy. Issue 1 (January 2021) - Yoshida, Mitsuhiro; Ono, Shigehiro; Shimizu, Yoshitaka; Oue, Kana; Mukai, Akari; Doi, Mitsuru; Irifune, Masahiro
Abstract : Abstract: Tranexamic acid has been used to reduce intraoperative bleeding; however, its effect on anti-inflammation and the amount of drainage after orthognathic surgery is yet to be determined. Therefore, we aimed to examine the effect of tranexamic acid on intraoperative bleeding volume and operation time, amount of drainage, and anti-inflammation after orthognathic surgery. Forty healthy women who underwent bilateral sagittal split ramus osteotomy under general anesthesia participated in this study. The amount of intraoperative bleeding, the operation time, the amount of drainage, and the C-reactive protein level were compared between patients intravenously administered with tranexamic acid before surgery (before-surgery group) and those administered with the drug after surgery (after-surgery group). All data were analyzed using the Student t -test. Results were considered to be statistically significant when P < 0.05. Although no significant difference was found in the amount of drainage between the groups ( P > 0.05), significant variations were detected in the amount of bleeding during surgery (before-surgery group: 161.7 ± 45.3 mL versus after-surgery group: 270.2 ± 24.0 mL; P = 0.0009), operation time (before-surgery group: 141.3 ± 16.8 min versus after-surgery group: 166.8 ± 24.9 min; P = 0.03), and postoperative C-reactive protein level (before-surgery group: 3.77 ± 0.40 mg/dL versus after-surgery group: 5.02 ± 0.75 mg/dL; P = 0.012) between the groups. In conclusion, administering tranexamic acid before surgery was found to significantly decrease bleeding, reduce operation time, and suppress postoperative inflammation.